Systematic literature review of workplace environment studies at the Space Syntax Symposia 1-13 - Aydoğan, Hicret; Şalgamcioğlu, Mehmet Emin (European Spatial Research and Policy, 2026)
This systematic scoping review investigates the influence of spatial design on employee behaviour by analysing workplace research presented at the Space Syntax Symposia (SSS). Adhering to PRISMA guidelines, 37 articles from the 1st–13th SSS were analysed regarding their spatial, social, and methodological components. The study reveals correlations between analysis techniques, syntactic properties, and social behaviours. Although limited to symposium proceedings, the review demonstrates strong representativeness and operational consistency. Two primary contributions emerge: the identification of three contextual patterns mapping the relationship between syntactic metrics and behavioural phenomena across office types, and the establishment of a comprehensive empirical foundation connecting behaviour, perception, and metrics. This work provides a critical baseline for future meta-analyses and theoretical research in the field.